THE CONCEPT OF DRAWING IN FINE ARTS - Akhmadaliyeva Nilufar Kobuljon qizi (Bright Mind Publishing, 2025)
This article is devoted to highlighting the history of the origin of drawing, one of the important concepts in the field of fine arts, stages of development and its significance in modern art. The initial forms of drawing, its evolution in medieval and modern art, as well as its role in art and design today are analyzed. The article considers the aesthetic and functional aspects of drawing, its features as a means of artistic expression. The research is relevant for international scientific conferences and provides important information for specialists in the field of art criticism and fine arts.
Keywords: Drawing, fine arts, art history, aesthetics, artistic expression, modern art, graphic design.